A matter of survival? An exploratory study of cooperation and benefits for the South African maritime defence industry within the BRICS context - Beukes, Jacobus Petrus (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMil)--Stellenbosch University, 2021.